Etiological analysis, morbidities and mortality that affect the young and middle aged admitted with altered mental status in a general hospital - Naqash, Henna; Shah, Parvaiz Ahmad; Bhat, Mohammad Hayat; Dar, Ishrat Hussain; Maqbool, Muzaffar (International Journal of Advances in Medicine, 2018)
Background: Authors conducted this study to find the profile of causes and diseases that affect patients of younger age group in altered sensorium admitted in a general hospital associated with Government Medical College Srinagar, in India. Methods: Authors conducted present study over a period of eight months. The patients of young and middle age who were admitted in their hospital ward with altered mental status were included. The study subjects were divided into two groups: group A included patients of age upto 30 years, and group B with patients in age group 31-50 years. The patients were studied for their diagnoses, comorbidities, gender distribution, duration of stay in hospital and mortality patterns. Results: Authors had a total of 112 patients of young and middle age admitted in their hospital ward with altered mental status during the study period. In group A, there were 42 patients or 37.5% (20 males and 22 females). In group B, there were 70 patients or 62.5% (30 males and 40 females). The most common cause of admission in these patients was infection (29.46%) followed by seizures (17.85%) and cardioembolic strokes (11.60%). The most common comorbidities in studied patients were underlying seizure disorder, psychiatric disease in the form of bipolar affective disorder or schizophrenia, hypertension, type 2 diabetes and chronic kidney disease. There were 14 deaths in group A and 30 deaths in group B. The most common cause of death was infections followed by seizures, Acute respiratory distress syndrome (ARDS) and severe diabetic ketoacidosis (DKA). Conclusions: The most common cause of admission in young and middle-aged patients in authors’ hospital was infection followed by seizures and cardioembolic strokes. The most common cause of death was again infections followed by seizures, acute respiratory distress syndrome and severe diabetic ketoacidosis.